Effect of biofertilizers on growth, production and profitability of gobhi sarson (Brassica napus L.) at varying fertility levels (Journal of Oilseed Brassica, 2025)
A field experiment was conducted during rabi season of 2022-23 at Shivalik Agricultural Research and Extension Centre (SAREC), Kangra, Himachal Pradesh to assess the effect of biofertilizers on growth, production and profitability of gobhi sarson at varying fertility levels. The experiment was conducted in split-plot design comprises three fertility levels (Control, 75% of recommended dose of fertilizer and 100% RDF) as main plot treatments and biofertilizers (Azotobacter, phosphate solubilizing micro-organism (PSMO), potassium mobilizing biofertilizer (KMB), NPK consortia + zinc solubilizing biofertilizer (ZSB), ZSB and control (no biofertilizer)] as sub plots, replicated thrice. The experimental results revealed that application of 100% RDF recorded higher growth (plant height, dry matter accumulation), yield attributes viz. number of primary and secondary branches/plant, numberof siliquae/plant, number of seeds/siliqua and 1000-seed weight which resulted in significantly higher seed yield (1866 kg/ha), oil content (41.3%), oil yield (771.0 kg/ha) as well as gross returns (Rs 1,01,695/ha), net returns (Rs 62,819/ha) and B:C ratio (1.62). Azotobacter and PSMO exhibited most efficient biofertilizers with better plant growth in terms of plant height and dry matter accumulation. Seed inoculation with Azotobacter recorded significantly higher values of growth parameters, yield attributes, seed yield (1687 kg/ha), oil content (41.5%) and oil yield (703.5 kg/ha) besides recording higher gross returns (Rs 91,945/ha), net returns (Rs 59,250/ha) and B:C ratio (1.81) followed by PSMO.